(untitled) (Scientific Journal of Actuarial Finance and Accounting, 2024)
This study investigates the influence of staff appearance on customer satisfaction and loyalty in Uzbek restaurants. Using a mixed-method approach, including surveys and field observations, the research explores how the physical appearance of staff impacts customer perceptions and their subsequent loyalty. The findings suggest that well-groomed and professionally dressed staff are perceived as more competent and hospitable, which significantly enhances customer satisfaction and encourages repeat business.